2019
DOI: 10.3389/fmars.2019.00761
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of a Near Vessel Strike of a Blue Whale: Perceptual Cues and Fine-Scale Aspects of Behavioral Avoidance

Abstract: Whale Uses Cues to Avoid Ship-Strike integration of these methods and technologies demonstrates the capacity for detailed behavioral studies of blue whales and other highly mobile marine megafauna, which will contribute to more informed evaluation and mitigation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…5 ). The ability of blue whales to avoid approaching vessels appears to be limited to relatively slow descents/ascents, with no horizontal movements away from a vessel 102 , 103 , therefore, collision events might pose significant threats to survival and recovery 97 for this endangered population. As inner waters of NCP might be considered, at the time, the spot of higher relative and absolute probabilities of negative interactions between blue whales and vessels, management actions are urgently needed to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). The ability of blue whales to avoid approaching vessels appears to be limited to relatively slow descents/ascents, with no horizontal movements away from a vessel 102 , 103 , therefore, collision events might pose significant threats to survival and recovery 97 for this endangered population. As inner waters of NCP might be considered, at the time, the spot of higher relative and absolute probabilities of negative interactions between blue whales and vessels, management actions are urgently needed to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…First, since using a linear relationship between avoidance response with increasing vessel speed resulted in very similar mortality results as a logistic relationship (Rockwood et al, 2017), we chose to limit our analysis to only the logistic formulation of avoidance. Though the speed-avoidance relationship remains poorly understood (Szesciorka et al, 2019), observations, and analysis have best supported the logistic formulation (Gende et al, 2011). In previous versions of this model (Rockwood et al, 2017), mean ship parameters were calculated across all vessels within a grid cell prior to running the mortality model.…”
Section: Model Frameworkmentioning
confidence: 99%
“…Locations that were closer than 500 m to the vessel were also rejected because of the possibility of responsive movement. This distance was chosen based on qualitative observations during the voyages, on the analysis of Lesage et al (2017), who noted behavioural changes in blue whales in the St. Lawrence estuary Canada when vessels were within 400 m, and research by Szesciorka et al (2019) who reported a change in surfacing behaviour as a ship approached within 300m.…”
Section: Fine-scale Movement Within Track (Swim Speed and Heading)mentioning
confidence: 99%